EYE EXERCISE MENCEGAH KELELAHAN MATA MAHASISWA DI ERA DIGITAL - Zulfa Mahdiatur Rasyida; Laras Putri Yani; Moch. Achnaf Haydan Al Husain; Siska Purnama (Jurnal LENTERA, 2026)
Asthenopia, or eye strain, is a condition characterized by a decline in visual performance resulting from excessive accommodative effort, manifesting in ocular, musculoskeletal, and psychosocial symptoms. University students represent a vulnerable demographic due to the high intensity of digital device usage required for academic activities. Left untreated, this condition can lead to serious complications, including the degradation of visual acuity. This program aimed to provide education on the management of asthenopia through the implementation of practical eye exercises. The methods included video-based counseling, procedural demonstrations, and evaluation via return demonstration (redemonstration). Result Initial identification revealed that the predominant complaints were drowsiness during near-work activities (31.8%) and reading inefficiency (5.7%). Post-intervention evaluation indicated a positive response; 55.7% of participants reported that eye exercises were highly effective, while 36.4% found them somewhat helpful in alleviating fatigue. Furthermore, the objective of independence was achieved, with 79.5% of participants demonstrating the ability to perform the exercises independently. In conclusion, eye exercises serve as an effective intervention for reducing asthenopia symptoms and enhancing participant self-efficacy. This program is recommended as a sustainable, self-managed preventive strategy for university students in the digital era.